The value of metagenomic next-generation sequencing in the diagnosis of fever of unknown origin - Lan Min Lai; Qing-gen Chen; Yang Liu; Rui Zhao; Mei Ling Cao; Lei Yuan (Scientific Reports)
Abstract Fever of unknown origin (FUO) caused by infection is a disease state characterized by complex pathogens and remains a diagnostic dilemma. Metagenomic next-generation sequencing (mNGS) technology is a promising diagnostic tool for identifying pathogenic microbes of FUO caused by infection. Little is known about the clinical impact of mNGS in the etiological diagnosis of FUO. This study focuses on the value of mNGS in the etiologic diagnosis of FUO by diagnostic performance, further clarifying the value of mNGS in clinical management. In a single-centre retrospective cohort study, 263 FUO patients who underwent both mNGS and culture at the First Affiliated Hospital of Nanchang University were enrolled from December 2020 to February 2023. The sensitivity and specificity of culture and mNGS were analyzed based on the final clinical diagnosis as the gold standard to assess the diagnostic value of mNGS in FUO cases. Among the 263 patients, 69.96%(184/263) cases were diagnosed as infectious diseases, of which lower respiratory tract infections were the most common, accounting for 53.26%(98/184). 30.04%(79/263) cases had a diagnosis of non-infectious disease. From these cases, mNGS identified 150 true-positive cases, 21 false-positive cases, 58 true-negative cases, and 34 false-negative cases. The sensitivity of mNGS in infection diagnosis was much higher than that of culture [81.52%(150/184) vs. 47.28%(87/184)], but the specificity was the opposite[73.42%(58/79) vs. 84.81%(67/79)]. mNGS had a receiver operating characteristic (ROC) curve of 0.775 for infectious disease, which was significantly higher than that of culture (0.661, P < 0.05). mNGS detection revealed that bacteria were the most commonly identified potential pathogens. The top causative pathogens identified were Acinetobacter baumannii. Of the 263 patients with FUO, clinical management of 48.67% (128/263) patients was positively affected by mNGS, and 51.33% (135/263) patients were not affected by mNGS(P = 0.1074). To sum up, infectious diseases are the principal cause of FUO. mNGS could significantly improve the detected pathogen spectrum of FUO caused by infection. However, the FUO disease spectrum is relatively broad, including a large number of non-infectious diseases. Therefore, Further investigation is warranted into the specific clinical scenarios for which mNGS may offer the greatest clinical diagnostic value.